The impact of various scaffold components on vascularized bone constructs - Eweida, Ahmad; Schulte, Matthias; Frisch, Oliver; Kneser, Ulrich; Harhaus-Wähner, Leila (Journal of cranio-maxillofacial surgery, 2017)
Bone tissue engineering is gaining more interest in the field of craniofacial surgery where continuous efforts are being made to improve the outcomes via modulation of the scaffold components. In an in vitro three dimensional (3D) culture, the effect of bone morphogenic protein 2 (BMP2, 60 μg/ml) and the effect of different cell seeding densities (0.25, 0.5, and 1 × 104) of rat mesenchymal stem cells seeded on nanocrystalline hydroxyapatite in silica gel matrix (Nanobone®) on the cell viability and differentiation were studied. Alkaline phosphatase and viability assays were performed at day 7, day 14, and day 21 to assess the differentiation and the relative fraction of viable cells in the 3D cell cultures. In a subsequent in vivo study, we examined the effect of axial vascularization, the scaffold's particle size and the nature of the matrix (collagen type I vs. diluted fibrin) on vascularization and tissue generation in vascularized bone construct in rats. Regarding vascularization, we compared constructs vascularized randomly by extrinsic vascularization from the periphery of the implanted construct with others vascularized axially via an implanted arteriovenous loop (AVL). Regarding the particle size, we compared constructs having a scaffold particle size of 0.2 mm (powder) with other constructs having a particle size of 2 × 0.6 mm (granules). Regarding the matrix we compared constructs having a collagen matrix with others having a fibrin matrix. Various groups were compared regarding the amount of tissue generation, vascularization, and cellular proliferation. The initial seeding density had a temporary and minimal effect on the overall osteogenic differentiation of the cells. On the contrary, adding BMP2 in a concentration of 60 μg/ml over one week led to an overall enhanced osteogenic differentiation despite depressed cell viability. Axial vascularization was mandatory for efficient tissue formation and vascularization of the bone construct. Collagen matrix and a smaller particle size provided more favorable results in terms of vascularization and tissue formation than diluted fibrin and larger Nanobone particles.